5x+3=-2x+17

Simple and best practice solution for 5x+3=-2x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+3=-2x+17 equation:


Simplifying
5x + 3 = -2x + 17

Reorder the terms:
3 + 5x = -2x + 17

Reorder the terms:
3 + 5x = 17 + -2x

Solving
3 + 5x = 17 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
3 + 5x + 2x = 17 + -2x + 2x

Combine like terms: 5x + 2x = 7x
3 + 7x = 17 + -2x + 2x

Combine like terms: -2x + 2x = 0
3 + 7x = 17 + 0
3 + 7x = 17

Add '-3' to each side of the equation.
3 + -3 + 7x = 17 + -3

Combine like terms: 3 + -3 = 0
0 + 7x = 17 + -3
7x = 17 + -3

Combine like terms: 17 + -3 = 14
7x = 14

Divide each side by '7'.
x = 2

Simplifying
x = 2

See similar equations:

| (x-81)= | | 5x+3=-2c+17 | | 3y+6=5y-2 | | -14=(10-(3x-7)-8x) | | 3-x=x+7 | | 3/5x2/1= | | 2x+(x+4)=2 | | log(y-37)=5x | | 7x=-310+3x | | 9y+2=10y-5 | | X^2-36+7(x+6)=0 | | 3(x-5)+8=2(9-x) | | 4(2x-1.4)=3x-5.6 | | 2x=-3x+26 | | 2(1-k)x^2-4kx+k=0 | | cos^2x=0.5 | | y=9x^4/3x^2 | | 5a+8=3+6a | | 2k-3=6 | | 5/7m-1/2=4/5 | | 3x+9=5x-21 | | 4/9m=8 | | sinx=0.65 | | (9d^2+2d+4)y=0 | | (1-d)x+(1-d)(x+1)= | | (4/3)3.14r^3 | | 74-39=2 | | 3y+16=7y | | a^3+2a^2-a=2 | | t=s+ys | | 8x-5y+5z=1 | | t=s+yfors |

Equations solver categories